Prevalence of Color Vision Deficiency among Students in Hajand and Amad High Schools in Shekhan City - Abdulrahman, Masood Abdulkareem (Kurdistan Journal of Applied Research, 2017)
Color vision deficiency is a condition affecting human’s ability to see or recognize specific colors. It is mostly genetic, X-linked recessive inheritance and thus, is more common among males than females. This cross sectional study was done to find the prevalence of color vision deficiency among high school students in Shekhan city and to find the relation of color vision deficiency with different races. The study has been conducted in two high schools that were present inside Shekhan city at the time of the study (Amad high school for males and Hajand high school for females). All students screened by using Ishihara 24 plates.640 students (283 males, 357 females) were screened. Students’ age range (15-22 years), the Mean age for males17.50 years and for females 17.13 years. The prevalence of Color Vision Deficiency was 6.36% among males and 0.84% among females. The most common types of Color Vision Deficiency among males were deuteranomaly (10cases),protanomaly (5 cases), deuteranopia (2 cases) and protanopia (1 case). There was no significant difference between races and color vision deficiency. Similar to dyslexia, before it was well known and well understood, color vision deficiency is aninvisible disability and can lead to students becoming disappointment with learning or feeling that they are moronic or less cable than others. It can provide erroneous rules for learning and indeed, even influence how well they do in their exams and consecutively their choice of career.